Design of a Village Fund Management Information System in Gebang Village - Alya Azhar Fauziah; Sharyanto Sharyanto; Beranadus Gunawan Sudarsono (Yayasan Bina Internusa Mabarindo, 2022)
Allocation of Village Funds is one form of financial relationship between levels of government, namely the financial relationship between the district government and the village government . To formulate appropriate financial relationships, it is necessary to understand the authority of the village government, the separation in structuring the village financial business is not only on the desire to delegate authority and financing from the central government to local governments and the lack of professionalism of government officials in managing village finances. In connection with the late delegation of village financial management independently by the village, hereinafter referred to as the Village Fund Allocation. Based on several conditions in the management of village funds, managing the village fund allocation document database properly is very important because it will affect public confidence in the performance of village officials on the funds received from the village. Gebangmekar Village is one of the villages in Gebang District in Cirebon Regency. While the system modeling uses the Unified Modeling Language (UML) method using the PHP programming language, the database management system used is MySQL as well as the database. This Village Fund Management Information System is intended to be one of the solutions that can be used to simplify the process that runs in fast and effective fund management so that it can help improve the fund management process in Gebangmekar village, Gebang district, Cirebon regency.